Effects of Age and Body Size on Ovarian Development and Fecundity in Culex quinquefasciatus (Diptera: Culicidae) (Bangladesh Journal of Zoology, 2025)
Abstract not availableBangladesh J. Zool. 53(2): 231-235, 2025